PENGARUH ATRIBUT PRODUK WISATA, ELECTRONIC WORD OF MOUTH DAN PROMOSI TERHADAP KEPUTUSAN BERKUNJUNG KE OBYEK WISATA BRUJUL ADVENTURE PARK KEBUMEN - Siti nur azizah (LPPM Universitas Bina Sarana Informatika, 2019)
This research aims to test the effect of tourism product attributs, electronic word of mouth and promotion of tourist decision to visiting tourist attraction Brujul Adventure Park Kebumen. This research is motivated by a in the increasing number of tourists who visited that attraction Brujul Adventure Park (BAP) Kebumen.The collection of data by using a questionnaires with a number of samples 100 respondents who visited attraction Brujul Adventure Park (BAP) and find out Brujul Adventure Park (BAP) information via internet. This research method, using the technique of non-probability sampling with purposive sampling method. Data obtained from questionnaires, then processed and analyzed using multiple linear regression analysis through the SPSS 23 software.The result of this research shows that independent variables the tourism product attributs, and electronic word of mouth has a positive and significant effect on the dependent variable that is the decision to visit by using t test. While the attributes of tourism products have no significant effect on the decision of visiting by using t test. Then through f test shows that the three independent variables are proper to examine the dependent variable. Adjusted R Square of 0,683 shows that the independent variables can explain 68,3% the dependent variable that is decision to visit, while the remaining 31,7% is explained by other variables outside of variable that used in this research.